ANALISIS REAKSI INVESTOR TERHADAP PENGUMUMAN RIGHT ISSUE DAN PENGUMUMAN LABA DI BURSA EFEK INDONESIA (BEI) (Studi Pada Perusahaan Manufaktur Yang Terdaftar di BEI Pada Tahun 2017-2019) - Nur Susanto; Noor Shodiq Askandar; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2020)
ABSTRAKThis study aims to analyze investors' reactions to the announcements of rights issues and earnings announcements on the stock exchange. Hypothesis testing using regression analysis. Research using secondary data from www.idx.com. This study uses 6 manufacturing companies that have been selected through the documentation method. for three years. Hypothesis testing using regression analysis. Simultaneously, Abnormal Return, Tranding Volume, there is a difference in Return before and after the announcement of the Right Issue. Based on the results of the Paired Sample t-test, there is no difference in Tranding Volume Activity before and after the announcement of Profit. Keywords: Investor Reaction, Right Issue Announcement and Profit Announcement